2015
DOI: 10.12669/pjms.312.6686
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preemptive analgesia with intravenous oxycodone in the patients undergoing laparoscopic resection of ovarian tumor

Abstract: Objective:To evaluate the efficacy of preemptive intravenous oxycodone in the patients undergoing laparoscopic resection of ovarian tumor.Methods:Sixty ASA I or II patients undergoing elective laparoscopic resection of ovarian tumor were randomly allocated to one of two groups: Group O (n=30) received intravenous oxycodone (0.1 mg·kg-1) 10 minutes before surgery over 2 minutes, and Group N (n=30) received an equivalent volume of normal saline. All patients received a standardized general anesthesia. MBP and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…24 A clinical study suggested that preemptive administration of oxycodone 0.1 mg/kg could effectively depress the stress response and was conducive to maintain intraoperative hemodynamic stability. 11 Moreover, Park et al 25 also revealed that the hemodynamics changes could be attenuated by pretreatment of 0.1 mg/kg intravenous oxycodone during the induction period. Therefore, we selected the dosage of oxycodone 0.1 mg/kg for preemptive analgesia, which is also the usual dosage of preemptive administration in our center.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 A clinical study suggested that preemptive administration of oxycodone 0.1 mg/kg could effectively depress the stress response and was conducive to maintain intraoperative hemodynamic stability. 11 Moreover, Park et al 25 also revealed that the hemodynamics changes could be attenuated by pretreatment of 0.1 mg/kg intravenous oxycodone during the induction period. Therefore, we selected the dosage of oxycodone 0.1 mg/kg for preemptive analgesia, which is also the usual dosage of preemptive administration in our center.…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing noncardiac surgery, the equivalent dose of sufentanil and oxycodone is 1:750 to 1000 . A clinical study suggested that preemptive administration of oxycodone 0.1 mg/kg could effectively depress the stress response and was conducive to maintain intraoperative hemodynamic stability . Moreover, Park et al also revealed that the hemodynamics changes could be attenuated by pretreatment of 0.1 mg/kg intravenous oxycodone during the induction period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 - 5 Compared with morphine, hydromorphone may be the ideal intravenous opioid for preemptive analgesia because it is approximately 7 times more potent and has a faster onset, due to its increased lipophilia. 6 , 7 According to previous studies, 2 , 4 , 5 preemptive opioid decrease hemodynamic changes, pain intensity and morphine consumption without increased side effects. To the best of our knowledge, no comprehensive data have been found with regard to efficacy of preoperative hydromorphone, so we design this prospective, double-blinded, randomized and parallel clinical research to evaluate it.…”
mentioning
confidence: 94%
“…However, it also increases the incidence of postoperative nausea and vomiting. [10] Oxycodone is a semi-synthetic opioid analgesic, which can effectively relieve visceral pain by stimulating µ and κ receptors, especially κ receptors, and it has fewer adverse reactions than other opioid drugs. [11,12] Studies have shown that both µ and κ receptors exist in the gastrointestinal tract, and their functions include controlling visceral pain.…”
Section: Introductionmentioning
confidence: 99%